Composite flame-retardant cable sheath material for medium and high voltage cables and method for producing the same

CN120904561BActive Publication Date: 2026-10-23山东正达电缆有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511267415.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2026-10-23
Estimated Expiration
2045-09-05

AI Technical Summary

Technical Problem

[0004]为了克服上述的技术问题,本发明的目的在于提供一种中高压电缆用复合阻燃电缆护套材料及其制备方法,解决了现有的电缆护套材料属于易燃材料,难以满足高防火要求,这对电力系统的安全构成了严重威胁的问题

Benefits of technology

本发明通过将聚乙烯树脂、乙烯-醋酸乙烯共聚物、复合阻燃料、润滑剂、增塑剂、抗氧剂、紫外线吸收剂以及光稳定剂进行搅拌混合,得到预混料,将预混料进行熔融混合,经挤出、水冷、切粒,得到中高压电缆用复合阻燃电缆护套材料;本发明采用将氮化植酸螯合钡化合物、含硼硅溶胶进行合理复配作为复合阻燃剂,两者均具有优异的阻燃性能,将复合阻燃剂加入至电缆护套材料中,在两种协同阻燃效应下,能够显著提升电缆护套材料的阻燃性能,有效减少了火灾的发生和扩散风险,提高了电缆系统的安全性和可靠性,而且,电缆护套材料的制备工艺简单可控,适合工业化大规模生产,具有良好的应用前景。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of cable sheath material, specifically to a kind of composite flame-retardant cable sheath material for medium and high voltage cable and its preparation method, for solving the problem that the existing cable sheath material is flammable material, it is difficult to meet the high fireproof requirement, which constitutes serious threat to the safety of power system;The present application adopts to reasonably compound nitrogenated phytate chelated barium compound and boron-containing silica sol as composite flame retardant, both have excellent flame retardant performance, add composite flame retardant into cable sheath material, under the synergistic flame-retardant effect of two, the flame retardant performance of cable sheath material can be significantly improved, the occurrence and spread risk of fire is effectively reduced, the safety and reliability of cable system are improved, moreover, the preparation process of cable sheath material is simple and controllable, suitable for industrial large-scale production, has good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable sheath materials, specifically to a composite flame-retardant cable sheath material for medium and high voltage cables and its preparation method. Background Technology

[0002] Medium and high voltage cables, as key equipment for power transmission, are widely used in urban power grids, rail transit, energy and chemical industries. However, due to the high operating voltage they withstand, medium and high voltage cables are prone to fires in the event of short circuits or overloads. Traditional cable sheath materials are flammable and often fail to meet high fire resistance requirements, posing a serious threat to the safety of power systems. Therefore, developing a composite flame-retardant cable sheath material for medium and high voltage cables and its preparation method is of great significance for improving the safety and stability of power systems.

[0003] To address the aforementioned technical shortcomings, a solution is proposed. Summary of the Invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a composite flame-retardant cable sheath material for medium and high voltage cables and its preparation method, which solves the problem that existing cable sheath materials are flammable materials and cannot meet high fire protection requirements, which poses a serious threat to the safety of power systems.

[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following components by weight: The composition includes 72-76 parts of polyethylene resin, 21-25 parts of ethylene-vinyl acetate copolymer, 1.5-5.5 parts of composite flame retardant, 0.5-1.1 parts of lubricant, 4-8 parts of plasticizer, 1-3 parts of antioxidant, 0.3-0.5 parts of ultraviolet absorber, and 0.6-1 parts of light stabilizer. The composite flame retardant includes barium nitride phytic acid chelate compound and boron-containing silica sol; The nitrided phytic acid chelated barium compound is prepared by the following steps: Step a1: Add phytic acid solution and 2-bromoethanol to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Stir the reaction at 20-25℃ and 200-300 r / min for 10-20 min. Then raise the temperature to 130-140℃ and continue stirring for 3-5 h. After the reaction is complete, cool the reaction product to room temperature and then place it in a vacuum drying oven at 50-60℃ for 3-5 h to obtain brominated phytic acid. Step a2: Add phytic acid bromide, 5-aminotetrazolium, triethylamine, and ethanol solution to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Purge with nitrogen for protection and stir the reaction at 20-25℃ and 200-300 r / min for 10-20 min. Then, heat to reflux and continue stirring for 3-5 h. After the reaction is complete, cool the reaction product to room temperature, then filter under vacuum. Remove the solvent by rotary evaporation of the filtrate, wash 3-5 times with anhydrous ethanol, and then place it in a vacuum drying oven at 60-70℃ for 2-3 h to obtain phytic acid bromide. Step a3: Add nitrogenized phytic acid and deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir the reaction at 20-25℃ and 200-300 r / min for 20-30 min. Then raise the temperature to 80-85℃ and continue stirring for 3-5 min. Then add barium chloride solution dropwise while stirring, controlling the dropping rate to 1-3 drops / s. After the addition is complete, continue stirring for 4-6 h. After the reaction is complete, cool the reaction product to room temperature, then filter under vacuum. Wash the filter cake 3-5 times with distilled water, then place it in a vacuum drying oven and dry at 60-70℃ for 5-6 h to obtain nitrogenized phytic acid chelated barium compound.

[0006] In a preferred embodiment of the present invention, the ratio of phytic acid solution to 2-bromoethanol in step a1 is 20g:1.2-3.5g.

[0007] In a preferred embodiment of the present invention, the phytic acid solution in step a1 has a mass fraction of 60-70%.

[0008] In a preferred embodiment of the present invention, the ratio of phytic acid bromide, 5-aminotetrazolium, triethylamine and ethanol solution in step a2 is 10g:0.7-1.9g:40-50mmol:70-80mL.

[0009] In a preferred embodiment of the present invention, the volume fraction of the ethanol solution in step a2 is 50-70%.

[0010] In a preferred embodiment of the present invention, the ratio of nitrogenized phytic acid, deionized water and barium chloride solution in step a3 is 10g: 50-60mL: 90-100mL.

[0011] In a preferred embodiment of the present invention, the barium chloride solution in step a3 is a solution formed by dissolving barium chloride in deionized water at a ratio of 3-7g: 50-55mL.

[0012] In a preferred embodiment of the present invention, the boron-containing silica sol is prepared by the following steps: Tetraethoxysilane, boric acid, and anhydrous ethanol were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Nitrogen gas was introduced for protection, and the mixture was stirred for 10-15 minutes at a temperature of 20-25℃ and a stirring rate of 200-300 r / min. The temperature was then raised to 70-75℃ and the reaction was continued with stirring for 3-5 hours. Hydrochloric acid solution was then added dropwise while stirring, with the dropping rate controlled at 1-3 drops / s. After the addition was completed, the temperature was raised to 80-85℃ and the reaction was continued with stirring for 2-3 hours. After the reaction was completed, the reaction product was cooled to room temperature to obtain borosilicate sol.

[0013] In a preferred embodiment of the present invention, the ratio of tetraethoxysilane, boric acid, anhydrous ethanol and hydrochloric acid solution is 45-50 mL: 2-5 g: 18-20 mL: 5-5.5 mL.

[0014] In a preferred embodiment of the present invention, the molar concentration of the hydrochloric acid solution is 0.01-0.05 mol / L.

[0015] Secondly, this application provides a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step 1: Weigh out 72-76 parts of polyethylene resin, 21-25 parts of ethylene-vinyl acetate copolymer, 1.5-5.5 parts of composite flame retardant, 0.5-1.1 parts of lubricant, 4-8 parts of plasticizer, 1-3 parts of antioxidant, 0.3-0.5 parts of ultraviolet absorber, and 0.6-1 parts of light stabilizer according to the following weight proportions, and set aside for later use; Step 2: Add polyethylene resin, ethylene-vinyl acetate copolymer, composite flame retardant, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer into a high-speed mixer, and stir and mix for 10-30 minutes at a temperature of 60-80℃ and a speed of 700-1500r / min to obtain a premix. Step 3: Add the premixed material to a twin-screw extruder and melt-mix it at a screw speed of 100-150 r / min and five temperature zones along the material conveying direction of 155-165℃, 165-175℃, 175-185℃, 185-195℃, and 180-190℃, respectively. After extrusion, water cooling, and pelletizing, the composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0016] In a preferred embodiment of the present invention, the polyethylene resin is LLDPE 318BJ.

[0017] In a preferred embodiment of the present invention, the ethylene-vinyl acetate copolymer is EVA V5110J.

[0018] In a preferred embodiment of the present invention, the composite flame retardant is a mixture of barium phytic acid chelate compound and boron-containing silica sol in a mass ratio of 0.9-3.5:7.

[0019] In a preferred embodiment of the present invention, the lubricant is ethylene bis-stearamide.

[0020] In a preferred embodiment of the present invention, the plasticizer is epoxidized soybean oil.

[0021] In a preferred embodiment of the present invention, the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 1-2:0.8.

[0022] In a preferred embodiment of the present invention, the ultraviolet absorber is ultraviolet absorber UV-531.

[0023] In a preferred embodiment of the present invention, the light stabilizer is Tinuvin 788.

[0024] Compared with the prior art, the beneficial effects of the present invention are: This invention involves mixing polyethylene resin, ethylene-vinyl acetate copolymer, composite flame retardant, lubricant, plasticizer, antioxidant, ultraviolet absorber, and light stabilizer to obtain a premix. The premix is ​​then melt-mixed, extruded, water-cooled, and pelletized to obtain a composite flame-retardant cable sheath material for medium and high voltage cables. This invention uses a rationally compounded composite flame retardant agent consisting of nitrided phytic acid chelated barium compound and boron-containing silica sol. Both possess excellent flame-retardant properties. Adding this composite flame retardant to the cable sheath material significantly improves its flame-retardant performance through a synergistic flame-retardant effect, effectively reducing the risk of fire occurrence and spread, and enhancing the safety and reliability of the cable system. Furthermore, the preparation process of the cable sheath material is simple and controllable, suitable for large-scale industrial production, and has promising application prospects.

[0025] In the preparation of cable sheath materials, a phytic acid chelated barium compound was first prepared. This was achieved through a reaction between phytic acid and 2-bromoethanol, where the phosphate group on phytic acid undergoes esterification with the hydroxyl group on 2-bromoethanol, simultaneously introducing bromine atoms to obtain brominated phytic acid. Then, a reaction between brominated phytic acid and 5-aminotetrazole was conducted, where both the bromine atom and the phosphate group on the brominated phytic acid react with the amino group on the 5-aminotetrazole, introducing a large amount of nitrogen into the phytic acid structure to obtain nitrified phytic acid. Subsequently, the phosphate group on the nitrified phytic acid formed a chelate with barium ions, grafting barium ions onto the phytic acid structure to obtain the phytic acid chelated barium compound. The molecular structure of this phytic acid chelated barium compound... Containing a large amount of phosphorus, it generates phosphoric acid, metaphosphoric acid, and other substances at high temperatures. The acid catalyzes the polymer to form a carbon layer that provides heat insulation and oxygen barrier, thus playing a flame-retardant role. At the same time, its molecular structure contains a large amount of nitrogen. The nitrogen and ammonia produced by thermal decomposition can dilute the oxygen concentration in the combustion zone, thus playing a flame-retardant role. In addition, its molecular structure contains a large amount of barium metal ions, which have the ability to catalyze the carbonization of combustion materials and can form a continuous, dense, highly graphitized, and structurally stable carbon layer. Therefore, under the synergistic effect of phosphorus, nitrogen, and barium metal ions, phytic acid chelated barium compounds are endowed with excellent flame-retardant properties. Adding them to cable sheath materials can give them a high flame-retardant effect.

[0026] In the process of preparing cable sheath materials, a boron-containing silica sol was also prepared. The boron-containing silica sol was synthesized by sol-gel method using tetraethoxysilane as the silicon source and boric acid as the boron source. The boron-containing silica sol forms a silicon-boron composite glassy substance at high temperature, which can fill the voids in the carbon layer, significantly improving the oxidation resistance and structural stability of the carbon layer. It can also form a dense ceramic protective layer, effectively blocking the transfer of heat and oxygen to the interior of the material. Adding it to the cable sheath material can inhibit the thermal decomposition and combustion of polymer materials at high temperature, slow down the spread of fire, and significantly improve the flame retardant performance of the cable sheath material. Detailed Implementation

[0027] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Example 1: This example describes a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step S1: Add 20g of 60% phytic acid solution and 1.2g of 2-bromoethanol to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 20℃ and 200r / min for 10min. Then raise the temperature to 130℃ and continue stirring for 3h. After the reaction is complete, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 50℃ for 3h to obtain brominated phytic acid. Step S2: 10g of phytic acid bromide, 0.7g of 5-aminotetrazolium, 40mmol of triethylamine, and 70mL of 50% ethanol solution were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 20℃ and 200r / min for 10min. Then, the mixture was heated to reflux and stirred for 3h. After the reaction was completed, the reaction product was cooled to room temperature, then vacuum filtered, and the solvent was removed by rotary evaporation of the filtrate. The filtrate was then washed three times with anhydrous ethanol and placed in a vacuum drying oven at 60℃ for 2h to obtain phytic acid bromide. Step S3: Add 10g of phytic acid nitrification and 50mL of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 20℃ and 200r / min for 20min. Then raise the temperature to 80℃ and continue stirring for 3min. While stirring, add 90mL of barium chloride solution (3g:50mL dissolved in deionized water) dropwise, controlling the dropping rate to 1 drop / s. After the addition is complete, continue stirring for 4h. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake three times with distilled water and then place it in a vacuum drying oven at 60℃ for 5h to obtain phytic acid chelated barium compound. Step S4: Add 45 mL of tetraethoxysilane, 2 g of boric acid, and 18 L of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 20 °C and 200 r / min for 10 min. Then raise the temperature to 70 °C and continue stirring for 3 h. Then, while stirring, add 5 mL of 0.01 mol / L hydrochloric acid solution dropwise at a rate of 1 drop / s. After the addition is complete, raise the temperature to 80 °C and continue stirring for 2 h. After the reaction is complete, cool the reaction product to room temperature to obtain borosilicate sol. Step S5: Weigh out 72 parts by weight of polyethylene resin, 21 parts by weight of ethylene-vinyl acetate copolymer, 1.5 parts by weight of composite flame retardant, 0.5 parts by weight of lubricant, 4 parts by weight of plasticizer, 1 part by weight of antioxidant, 0.3 parts by weight of UV absorber, and 0.6 parts by weight of light stabilizer, and set aside. The polyethylene resin is LLDPE 318BJ; the ethylene-vinyl acetate copolymer is EVA V5110J; the composite flame retardant is a mixture of nitrided phytic acid chelated barium compound and boron-containing silica sol in a mass ratio of 0.9:7; the lubricant is ethylene bis-stearamide; the plasticizer is epoxidized soybean oil; the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 1:0.8; the UV absorber is UV absorber UV-531; and the light stabilizer is light stabilizer Tinuvin 788. Step S6: Add polyethylene resin, ethylene-vinyl acetate copolymer, composite flame retardant, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer to a high-speed mixer and stir and mix for 10 minutes at 60℃ and 700r / min to obtain a premix. Step S7: Add the premixed material to a twin-screw extruder and melt-mix it under the conditions of a screw speed of 100 r / min and five temperature zones along the material conveying direction of 155℃, 165℃, 175℃, 185℃ and 180℃ respectively. After extrusion, water cooling and pelletizing, composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0029] Example 2: This example describes a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step S1: Add 20g of 65% phytic acid solution and 2.3g of 2-bromoethanol to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and 250r / min for 15min. Then raise the temperature to 135℃ and continue stirring for 4h. After the reaction is complete, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 55℃ for 4h to obtain brominated phytic acid. Step S2: 10g of phytic acid bromide, 1.3g of 5-aminotetrazolium, 45mmol of triethylamine, and 75mL of 60% ethanol solution were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 22℃ and 250r / min for 15min. Then, the mixture was heated to reflux and stirred for 4h. After the reaction was completed, the reaction product was cooled to room temperature, then vacuum filtered, and the solvent was removed by rotary evaporation of the filtrate. The filtrate was then washed four times with anhydrous ethanol and placed in a vacuum drying oven at 65℃ for 2.5h to obtain phytic acid bromide. Step S3: Add 10g of phytic acid nitrification and 55mL of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 22℃ and 250r / min for 25min. Then raise the temperature to 82℃ and continue stirring for 4min. While stirring, add 95mL of barium chloride solution (5g:52mL dissolved in deionized water) dropwise, controlling the dropping rate at 2 drops / s. After the addition is complete, continue stirring for 5h. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake four times with distilled water and then place it in a vacuum drying oven at 65℃ for 5.5h to obtain phytic acid nitrification chelated barium compound. Step S4: Add 48 mL of tetraethoxysilane, 3.5 g of boric acid, and 19 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 22 °C and 250 r / min for 12 min. Then raise the temperature to 72 °C and continue stirring for 4 h. Then, while stirring, add 5.2 mL of 0.03 mol / L hydrochloric acid solution dropwise at a rate of 2 drops / s. After the addition is complete, raise the temperature to 82 °C and continue stirring for 2.5 h. After the reaction is complete, cool the reaction product to room temperature to obtain borosilicate sol. Step S5: Weigh out 74 parts by weight of polyethylene resin, 23 parts by weight of ethylene-vinyl acetate copolymer, 3.5 parts by weight of composite flame retardant, 0.8 parts by weight of lubricant, 6 parts by weight of plasticizer, 2 parts by weight of antioxidant, 0.4 parts by weight of UV absorber, and 0.8 parts by weight of light stabilizer, and set aside. The polyethylene resin is LLDPE 318BJ; the ethylene-vinyl acetate copolymer is EVA V5110J; the composite flame retardant is a mixture of nitrided phytic acid chelated barium compound and boron-containing silica sol in a mass ratio of 2.2:7; the lubricant is ethylene bis-stearamide; the plasticizer is epoxidized soybean oil; the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 1.5:0.8; the UV absorber is UV absorber UV-531; and the light stabilizer is light stabilizer Tinuvin 788. Step S6: Add polyethylene resin, ethylene-vinyl acetate copolymer, composite flame retardant, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer to a high-speed mixer and stir and mix for 20 minutes at 70℃ and 1100r / min to obtain a premix. Step S7: Add the premixed material to a twin-screw extruder and melt-mix it under the conditions of a screw speed of 125 r / min and five temperature zones along the material conveying direction of 160℃, 170℃, 180℃, 190℃ and 185℃ respectively. After extrusion, water cooling and pelletizing, composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0030] Example 3: This example describes a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step S1: Add 20g of 70% phytic acid solution and 3.5g of 2-bromoethanol to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 20min. Then raise the temperature to 140℃ and continue stirring for 5h. After the reaction is completed, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 60℃ for 5h to obtain brominated phytic acid. Step S2: 10g of phytic acid bromide, 1.9g of 5-aminotetrazolium, 50mmol of triethylamine, and 80mL of 70% ethanol solution were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25℃ and a stirring rate of 300r / min for 20min. Then, the mixture was heated to reflux and stirred for another 5h. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The solvent was removed by rotary evaporation of the filtrate. The filtrate was then washed five times with anhydrous ethanol and placed in a vacuum drying oven at 70℃ for 3h to obtain phytic acid bromide. Step S3: Add 10g of phytic acid nitrification and 60mL of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 30min. Then, raise the temperature to 85℃ and continue stirring for 5min. While stirring, add 100mL of barium chloride solution (7g:55mL dissolved in deionized water) dropwise, controlling the dropping rate at 3 drops / s. After the addition is complete, continue stirring for 6h. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake 5 times with distilled water and then place it in a vacuum drying oven at 70℃ for 6h to obtain phytic acid nitrification chelated barium compound. Step S4: Add 50 mL of tetraethoxysilane, 5 g of boric acid, and 20 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 25 °C and a stirring rate of 300 r / min for 15 min. Then, raise the temperature to 75 °C and continue stirring for 5 h. After that, add 5.5 mL of 0.05 mol / L hydrochloric acid solution dropwise while stirring, controlling the dropping rate to 3 drops / s. After the addition is complete, raise the temperature to 85 °C and continue stirring for 3 h. After the reaction is complete, cool the reaction product to room temperature to obtain borosilicate sol. Step S5: Weigh out 76 parts by weight of polyethylene resin, 25 parts by weight of ethylene-vinyl acetate copolymer, 5.5 parts by weight of composite flame retardant, 1.1 parts by weight of lubricant, 8 parts by weight of plasticizer, 3 parts by weight of antioxidant, 0.5 parts by weight of UV absorber, and 1 part by weight of light stabilizer, and set aside. The polyethylene resin is LLDPE 318BJ; the ethylene-vinyl acetate copolymer is EVA V5110J; the composite flame retardant is a mixture of nitrided phytic acid chelated barium compound and boron-containing silica sol in a mass ratio of 3.5:7; the lubricant is ethylene bis-stearamide; the plasticizer is epoxidized soybean oil; the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 2:0.8; the UV absorber is UV absorber UV-531; and the light stabilizer is light stabilizer Tinuvin 788. Step S6: Add polyethylene resin, ethylene-vinyl acetate copolymer, composite flame retardant, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer to a high-speed mixer and stir and mix for 30 minutes at 80℃ and 1500r / min to obtain a premix. Step S7: Add the premixed material to a twin-screw extruder and melt-mix it under the conditions of a screw speed of 150 r / min and five temperature zones along the material conveying direction of 165℃, 175℃, 185℃, 195℃ and 190℃ respectively. After extrusion, water cooling and pelletizing, composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0031] Comparative Example 1: This comparative example illustrates a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step S1: Weigh out 76 parts by weight of polyethylene resin, 25 parts by weight of ethylene-vinyl acetate copolymer, 1.1 parts by weight of lubricant, 8 parts by weight of plasticizer, 3 parts by weight of antioxidant, 0.5 parts by weight of ultraviolet absorber, and 1 part by weight of light stabilizer, and set aside. The polyethylene resin is LLDPE 318BJ; the ethylene-vinyl acetate copolymer is EVA V5110J; the lubricant is ethylene bis-stearamide; the plasticizer is epoxidized soybean oil; the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 2:0.8; the ultraviolet absorber is ultraviolet absorber UV-531; and the light stabilizer is light stabilizer Tinuvin 788. Step S2: Add polyethylene resin, ethylene-vinyl acetate copolymer, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer to a high-speed mixer and stir and mix for 30 minutes at 80℃ and 1500r / min to obtain a premix. Step S3: Add the premixed material to a twin-screw extruder and melt-mix it under the conditions of a screw speed of 150 r / min and five temperature zones along the material conveying direction of 165℃, 175℃, 185℃, 195℃ and 190℃ respectively. After extrusion, water cooling and pelletizing, composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0032] Comparative Example 2: This comparative example illustrates a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step S1: Add 50 mL of tetraethoxysilane, 5 g of boric acid, and 20 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 25 °C and a stirring rate of 300 r / min for 15 min. Then, raise the temperature to 75 °C and continue stirring for 5 h. After that, add 5.5 mL of 0.05 mol / L hydrochloric acid solution dropwise while stirring, controlling the dropping rate to 3 drops / s. After the addition is complete, raise the temperature to 85 °C and continue stirring for 3 h. After the reaction is complete, cool the reaction product to room temperature to obtain borosilicate sol. Step S2: Weigh out 76 parts by weight of polyethylene resin, 25 parts by weight of ethylene-vinyl acetate copolymer, 5.5 parts by weight of borosilicate sol, 1.1 parts by weight of lubricant, 8 parts by weight of plasticizer, 3 parts by weight of antioxidant, 0.5 parts by weight of UV absorber, and 1 part by weight of light stabilizer, and set aside. The polyethylene resin is LLDPE 318BJ; the ethylene-vinyl acetate copolymer is EVA V5110J; the lubricant is ethylene bis-stearamide; the plasticizer is epoxidized soybean oil; the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 2:0.8; the UV absorber is UV-531; and the light stabilizer is Tinuvin 788. Step S3: Add polyethylene resin, ethylene-vinyl acetate copolymer, boron silica sol, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer to a high-speed mixer and stir and mix for 30 minutes at 80℃ and 1500r / min to obtain a premix. Step S4: Add the premixed material to a twin-screw extruder and melt-mix it under the conditions of a screw speed of 150 r / min and five temperature zones along the material conveying direction of 165℃, 175℃, 185℃, 195℃ and 190℃ respectively. After extrusion, water cooling and pelletizing, composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0033] Comparative Example 3: This comparative example illustrates a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step S1: Add 20g of 70% phytic acid solution and 3.5g of 2-bromoethanol to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 20min. Then raise the temperature to 140℃ and continue stirring for 5h. After the reaction is completed, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 60℃ for 5h to obtain brominated phytic acid. Step S2: 10g of phytic acid bromide, 1.9g of 5-aminotetrazolium, 50mmol of triethylamine, and 80mL of 70% ethanol solution were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25℃ and a stirring rate of 300r / min for 20min. Then, the mixture was heated to reflux and stirred for another 5h. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The solvent was removed by rotary evaporation of the filtrate. The filtrate was then washed five times with anhydrous ethanol and placed in a vacuum drying oven at 70℃ for 3h to obtain phytic acid bromide. Step S3: Add 10g of phytic acid nitrification and 60mL of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 30min. Then, raise the temperature to 85℃ and continue stirring for 5min. While stirring, add 100mL of barium chloride solution (7g:55mL dissolved in deionized water) dropwise, controlling the dropping rate at 3 drops / s. After the addition is complete, continue stirring for 6h. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake 5 times with distilled water and then place it in a vacuum drying oven at 70℃ for 6h to obtain phytic acid nitrification chelated barium compound. Step S4: Weigh out 76 parts by weight of polyethylene resin, 25 parts by weight of ethylene-vinyl acetate copolymer, 5.5 parts by weight of barium phytic acid chelate compound, 1.1 parts by weight of lubricant, 8 parts by weight of plasticizer, 3 parts by weight of antioxidant, 0.5 parts by weight of ultraviolet absorber, and 1 part by weight of light stabilizer, and set aside. The polyethylene resin is LLDPE 318BJ; the ethylene-vinyl acetate copolymer is EVA V5110J; the lubricant is ethylene bis-stearamide; the plasticizer is epoxidized soybean oil; the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 2:0.8; the ultraviolet absorber is ultraviolet absorber UV-531; and the light stabilizer is light stabilizer Tinuvin 788. Step S5: Add polyethylene resin, ethylene-vinyl acetate copolymer, barium phytic acid chelate compound, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer to a high-speed mixer and stir and mix for 30 minutes at 80℃ and 1500r / min to obtain a premix. Step S6: Add the premixed material to a twin-screw extruder and melt-mix it under the conditions of a screw speed of 150 r / min and five temperature zones along the material conveying direction of 165℃, 175℃, 185℃, 195℃ and 190℃ respectively. After extrusion, water cooling and pelletizing, composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0034] Comparative Example 4: This comparative example illustrates a method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables, comprising the following steps: Step S1: Add 50 mL of tetraethoxysilane, 5 g of boric acid, and 20 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Purge with nitrogen for protection and stir at 25 °C and a stirring rate of 300 r / min for 15 min. Then, raise the temperature to 75 °C and continue stirring for 5 h. After that, add 5.5 mL of 0.05 mol / L hydrochloric acid solution dropwise while stirring, controlling the dropping rate to 3 drops / s. After the addition is complete, raise the temperature to 85 °C and continue stirring for 3 h. After the reaction is complete, cool the reaction product to room temperature to obtain borosilicate sol. Step S2: Weigh out 76 parts by weight of polyethylene resin, 25 parts by weight of ethylene-vinyl acetate copolymer, 5.5 parts by weight of composite flame retardant, 1.1 parts by weight of lubricant, 8 parts by weight of plasticizer, 3 parts by weight of antioxidant, 0.5 parts by weight of UV absorber, and 1 part by weight of light stabilizer, and set aside. The polyethylene resin is LLDPE 318BJ; the ethylene-vinyl acetate copolymer is EVA V5110J; the composite flame retardant is a mixture of phytic acid and boron-containing silica sol in a mass ratio of 3.5:7; the lubricant is ethylene bis-stearamide; the plasticizer is epoxidized soybean oil; the antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 2:0.8; the UV absorber is UV absorber UV-531; and the light stabilizer is light stabilizer Tinuvin 788. Step S3: Add polyethylene resin, ethylene-vinyl acetate copolymer, composite flame retardant, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer to a high-speed mixer and stir and mix for 30 minutes at 80℃ and 1500r / min to obtain a premix. Step S4: Add the premixed material to a twin-screw extruder and melt-mix it under the conditions of a screw speed of 150 r / min and five temperature zones along the material conveying direction of 165℃, 175℃, 185℃, 195℃ and 190℃ respectively. After extrusion, water cooling and pelletizing, composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

[0035] The composite flame-retardant cable sheathing materials for medium and high voltage cables in Examples 1-3 and Comparative Examples 1-4 were tested for oxygen index according to ASTM D2863 standard and UL-94 rating according to ASTM D3801 standard. The test results are shown in the table below: .

[0036] Referring to the data in the table above, and based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that adding nitrided phytic acid chelated barium compound and boron-containing silica sol to the cable sheath material can significantly improve the flame retardant performance of the cable sheath material.

[0037] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0038] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.

Claims

1. A composite flame-retardant cable sheath material for medium and high voltage cables, characterized in that, Includes the following components by weight: The composition includes 72-76 parts of polyethylene resin, 21-25 parts of ethylene-vinyl acetate copolymer, 1.5-5.5 parts of composite flame retardant, 0.5-1.1 parts of lubricant, 4-8 parts of plasticizer, 1-3 parts of antioxidant, 0.3-0.5 parts of ultraviolet absorber, and 0.6-1 parts of light stabilizer. The composite flame retardant includes barium nitride phytic acid chelate compound and boron-containing silica sol; The nitrided phytic acid chelated barium compound is prepared by the following steps: Step a1: The phytic acid solution and 2-bromoethanol were stirred and reacted. After the reaction was completed, the reaction product was cooled and then dried to obtain brominated phytic acid. Step a2: Hyaluronic acid bromide, 5-aminotetrazolium, triethylamine and ethanol solution are stirred and reacted. After the reaction is completed, the reaction product is cooled, then vacuum filtered, the filtrate is evaporated by rotary evaporation, then washed and dried to obtain hyaluronic acid bromide. Step a3: Nitrogenized phytic acid and deionized water are stirred and reacted, and then barium chloride solution is added dropwise. After the addition is complete, the reaction is stirred and reacted. After the reaction is completed, the reaction product is cooled and then filtered under vacuum. The filter cake is washed and dried to obtain nitrified phytic acid chelated barium compound. The boron-containing silica sol was prepared by the following steps: Tetraethoxysilane, boric acid, and anhydrous ethanol were stirred and reacted. Then, hydrochloric acid solution was added dropwise. After the addition was complete, the reaction was stirred and reacted. After the reaction was completed, the reaction product was cooled to obtain boron-containing silica sol.

2. The composite flame-retardant cable sheath material for medium and high voltage cables according to claim 1, characterized in that, In step a1, the ratio of phytic acid solution to 2-bromoethanol is 20g:1.2-3.5g; the mass fraction of the phytic acid solution is 60-70%.

3. The composite flame-retardant cable sheath material for medium and high voltage cables according to claim 1, characterized in that, In step a2, the ratio of phytic acid bromide, 5-aminotetrazolium, triethylamine, and ethanol solution is 10g:0.7-1.9g:40-50mmol:70-80mL; the volume fraction of the ethanol solution is 50-70%.

4. The composite flame-retardant cable sheath material for medium and high voltage cables according to claim 1, characterized in that, In step a3, the ratio of nitrogenized phytic acid, deionized water, and barium chloride solution is 10g:50-60mL:90-100mL; the barium chloride solution is formed by dissolving barium chloride in deionized water at a ratio of 3-7g:50-55mL.

5. The composite flame-retardant cable sheath material for medium and high voltage cables according to claim 1, characterized in that, The ratio of tetraethoxysilane, boric acid, anhydrous ethanol, and hydrochloric acid solution is 45-50 mL: 2-5 g: 18-20 mL: 5-5.5 mL; the molar concentration of the hydrochloric acid solution is 0.01-0.05 mol / L.

6. A method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Weigh out 72-76 parts of polyethylene resin, 21-25 parts of ethylene-vinyl acetate copolymer, 1.5-5.5 parts of composite flame retardant, 0.5-1.1 parts of lubricant, 4-8 parts of plasticizer, 1-3 parts of antioxidant, 0.3-0.5 parts of ultraviolet absorber, and 0.6-1 parts of light stabilizer according to the following weight proportions, and set aside for later use; Step 2: Add polyethylene resin, ethylene-vinyl acetate copolymer, composite flame retardant, lubricant, plasticizer, antioxidant, ultraviolet absorber and light stabilizer into a high-speed mixer, and stir and mix for 10-30 minutes at a temperature of 60-80℃ and a speed of 700-1500r / min to obtain a premix. Step 3: Add the premixed material to a twin-screw extruder and melt-mix it at a screw speed of 100-150 r / min and five temperature zones along the material conveying direction of 155-165℃, 165-175℃, 175-185℃, 185-195℃, and 180-190℃, respectively. After extrusion, water cooling, and pelletizing, the composite flame-retardant cable sheath material for medium and high voltage cables is obtained.

7. The method for preparing a composite flame-retardant cable sheath material for medium and high voltage cables according to claim 6, characterized in that, The polyethylene resin is LLDPE 318BJ; The ethylene-vinyl acetate copolymer is EVA V5110J; The composite flame retardant is a mixture of barium phytic acid chelate compound and boron-containing silica sol in a mass ratio of 0.9-3.5:7; The lubricant is ethylene bis-stearamide; The plasticizer is epoxidized soybean oil; The antioxidant is a mixture of antioxidant 1010 and antioxidant 2246-S in a mass ratio of 1-2:0.8; The ultraviolet absorber is ultraviolet absorber UV-531; The light stabilizer is Tinuvin 788.

Citation Information

Patent Citations

  • Method for preparing boron-containing silane coupling agent copolymer

    CN110204732A

  • Flame-retardant smoke-suppression polyethylene sheath material for middle-high voltage cable and preparation method of flame-retardant smoke-suppression polyethylene sheath material

    CN118325218A

  • Phytic acid-based environment-friendly flame retardant

    CN118834502A

  • Intumescent nitrogen-phosphorus flame retardant and preparation method thereof

    CN119161379A